(untitled) (Semiárida, 2020)
Whole plant and its components dry matter of an experimental fodder corn population (crossing between Zea mays L. x Zea diploperennis I.) and a commercial hybrid was evaluated with respect to three plant densities (50.000; 65.000 y 80.000 plants.ha-1) and two row spacings (50 y 70 cm). No response to row spacing was found, and no interaction with plant density and genotype could be determined. The results showed interaction of plant density and genotype on dry matter production of whole and leaves. The experimental population responded to the lowest plant density (5 plant m^) with the highest whole plant and leaf dry matter, while the commercial hybrid produced higher dry matter at intermediate plant density (6.5 plant.m-2). Future studies will corroborate the information on dry matter production and evaluation of digestibility of plant material should be carried out to better characterize the potential of the experimental population.